Peran Penghulu dan Penyuluh Agama KUA Kecamatan Rambipuji Sebagai Katalis Dalam Menghindari Pernikahan Dini dan Meningkatkan Kualitas Pernikahan - Yussuli Yussuli (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study is based on the fact that in Rambipuji District, Jember, there are many early marriages and poor-quality marriages, so intervention from religious figures and counselors is needed. The purpose of this study is to evaluate the role of religious figures and counselors and how effective they are in realizing harmonious families and reducing the number of early marriages in the area. This study was conducted qualitatively, with interviews and thorough observations of religious figures, counselors, and newly married couples. The results of the study indicate that religious figures and counselors have an important role in providing effective education and counseling. However, there are still problems in implementing the program consistently. The results indicate that religious figures and counselors need increased capacity and support so that they can do their jobs better. To obtain larger data, quantitative research should be used, and specific approaches should be studied for different cultural contexts.